2007
DOI: 10.1002/jsfa.2799
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, storage stability and costing of α‐amylase‐treated maize–beans–groundnuts–bambaranuts complementary blend

Abstract: The effects of α-amylase treatment on physical properties, acceptability to mothers, and cost of roasted and extruded maize-beans-groundnuts-bambaranuts complementary porridge recipes were assessed prior to their industrial production. Storage stability of the extruded α-amylase-treated fortified blend was assessed at 2 weeks and 6 months by sensory evaluation, peroxide value, water activity and microbiological load. The use of α-amylase at 0.04% w/w enhanced porridge acceptability and resulted in 88% and 122%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…The observation that both WFL and WFC porridges were generally accepted agrees with previous observations that mothers often find complementary foods processed from locally available staples attractive (Mensa-Wilmot et al, 2001;Owino et al, 2007). It appears that, in addition to a sufficient energy density, sensory qualities of complementary food formulations corresponding to food preferences of mothers and their infants are of importance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The observation that both WFL and WFC porridges were generally accepted agrees with previous observations that mothers often find complementary foods processed from locally available staples attractive (Mensa-Wilmot et al, 2001;Owino et al, 2007). It appears that, in addition to a sufficient energy density, sensory qualities of complementary food formulations corresponding to food preferences of mothers and their infants are of importance.…”
Section: Discussionsupporting
confidence: 87%
“…Some previous studies have found that complementary food formulations with addition of sugar were found to be more tasty and appealing than those without sugar, indicating that inclusion of sugar not only increased the energy density of the porridge but enhanced the taste and characteristic improved flavour (Martin et al, 2010;Muhimbula et al, 2011). Owino et al, 2007 found that sweetness improved the acceptability of α-amylase-treated maize-beans-groundnuts-bambaranuts complementary blends. This shows that inclusion of sugar or sweetener is important in the acceptability of product by target groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The flours were mixed with water to make porridges for infant feeding, similar in consistency and appearance to those in current local use. In pilot work, porridges were found to be acceptable [16] to the local population and to displace other micronutrient-poor complementary or family foods but not to displace breast milk intake [17]. The energy density of the porridge prepared according to package directions (equivalent to 30g blended in 250 ml water) was 0.76 kcal/g; [18] protein represented 16% of energy.…”
Section: Methodsmentioning
confidence: 98%
“…Different weaning food combinations of maize soy flour had protein contents within the range of 9.49 -19.70% (Osundahunsi and Aworh 2002). A similar phenomenon of the cereal -legume multiple mix with a different recipe was used by other workers that resulted in a similar composition (Owino et al 2007).…”
Section: Compositionmentioning
confidence: 90%